How do research-intensive universities portray employability strategies? A review of their websites - Bennett, Dawn; Knight, E.; Divan, A.; Kuchel, L.; Horn, J.; van Reyk, D.; da Silva, K. (Sage Publications, 2017)
Employability development is a strategic priority for universities across advanced western economies. Despite this, there is no systematic study of employability development approaches internationally. In this study, we considered how universities portray employability on the public pages of their websites. We undertook website content analysis of 107 research-intensive universities in Australia, Canada, the United Kingdom and the United States. Following Farenga and Quinlan, we classified these strategies as Portfolio, Hands-off, Award and Non-embedded. Portfolio or Award strategies were the most common across all four locations; Hands-off and Non-embedded strategies were more common to US universities; and Award was more common in the United Kingdom. Universities focused on either possessional or positional approaches to employability. We advocate for a pedagogical shift towards processual approaches in which responsibility for employability development is shared.